If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying t + t + t = 2(t + -2) Combine like terms: t + t = 2t 2t + t = 2(t + -2) Combine like terms: 2t + t = 3t 3t = 2(t + -2) Reorder the terms: 3t = 2(-2 + t) 3t = (-2 * 2 + t * 2) 3t = (-4 + 2t) Solving 3t = -4 + 2t Solving for variable 't'. Move all terms containing t to the left, all other terms to the right. Add '-2t' to each side of the equation. 3t + -2t = -4 + 2t + -2t Combine like terms: 3t + -2t = 1t 1t = -4 + 2t + -2t Combine like terms: 2t + -2t = 0 1t = -4 + 0 1t = -4 Divide each side by '1'. t = -4 Simplifying t = -4
| 5+4z-2=7z+8-2z | | 80-6=10x+16 | | 6y+3=7y-4 | | 5-x=4(5-x) | | (2n+4)+(n-3)=3n+1 | | 2(x-1)=4(x+1) | | -13=-2h-7 | | 2*x+3=3*(x-2) | | 4x+7x-9x=2x | | 3(10-5x)=8 | | 5p-2=6p+7 | | -23-4x=7-4x | | 58-6=3x+17 | | 3t-6=9-2t | | 233-7x=29x+21 | | 3.4x+8.7=1.7x+18.9 | | 10x+10=20x+20 | | x^5-x^3+x+1=0 | | 3x+x+2=2x-4 | | 31-9(y+5)=7 | | x^3-96x^2+576x=0 | | -17-9=8x+17 | | 7y-9=33 | | 4x24= | | 5(2x-1)+16=8x+1 | | 3x+1=2x-1 | | -24=6a-15-15a | | 10-10x=75-45x | | 5x-4=-4+5x | | x^4-x^3+1=0 | | 5x=4(x+3) | | 5a-9=26 |